A review of fetal and neonatal consequences of maternal systemic lupus erythematosus. (10th May 2020) - Limaye, Meghana A.; Buyon, Jill P.; Cuneo, Bettina F.; Mehta‐Lee, Shilpi S.
Abstract: Systemic lupus erythematosus (SLE) primarily affects women of childbearing age and is commonly seen in pregnancy. The physiologic and immunologic changes of pregnancy may alter the course of SLE and impact maternal, fetal, and neonatal health. Multidisciplinary counseling before and during pregnancy from rheumatology, maternal fetal medicine, obstetrics, and pediatric cardiology is critical. Transplacental passage of autoantibodies, present in about 40% of women with SLE, can result in neonatal lupus (NL). NL can consist of usually permanent cardiac manifestations, including conduction system and myocardial disease, as well as transient cutaneous, hematologic, and hepatic manifestations. Additionally, women with SLE are more likely to develop adverse pregnancy outcomes such as preeclampsia, fetal growth restriction, and preterm birth, perhaps due to an underlying effect on placentation. This review describes the impact of SLE on maternal and fetal health by trimester, beginning with prepregnancy optimization of maternal health. This is followed by a discussion of NL and the current understanding of the epidemiology and pathophysiology of anti‐Ro/La mediated cardiac disease, as well as screening, treatment, and methods for prevention. Finally discussed is the known increase in preeclampsia and fetal growth issues in women with SLE that can lead to iatrogenic preterm delivery.